Antimicrobial sensitivity pattern of bacterial isolates from Buffaloe affected with postpartum metritis - ABDULLAH, FAYAZ; TIWARl, R P; HIRPURKAR, S D (The Indian Journal of Animal Reproduction, 2007)
Isolation and identification of bacterial isolates from uterine discharge of 40 postpartum Murrah buffaloes affected with metritis revealed Corynebacterium (40%) as a major isolate followed by E. coli (32.5%), Staphylococcus (27.5%), Streptococcus (25%), Pseudomonas (7.5%), Proteus (5%) and Bacillus (5%). Antimicrobial test showed maximum sensitivity to ciprofloxacin (82.45%) and oxytetracycline (78.94%) followed by gentamycin (73.94%), choramphenicol (66.66%), cephalexin (50.87%), metronidazole (19.29%) and nitrofurazone (15.78%).